Language View of the World and Theory of Concept - qizi, Saydakhmatova Hilola Ibrokhim (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the theory of concept and related phenomena in modern cognitive linguistics. In modern cognitive linguistics, great emphasis is given on the study of the essence of a concept. Understanding the essence of a concept helps to explore a range of different interrelated concepts and terms. Consequently, the formation of concepts is related to the knowledge of the world, the formation of perceptions about it.